2019
DOI: 10.1186/s13293-019-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth outcomes following peri-implantation exposure of Long-Evans rats to noise and ozone differ by sex

Abstract: BackgroundExposure to air pollution and high levels of noise have both been independently associated with the development of adverse pregnancy outcomes including low birth weight. However, exposure to such environmental stressors rarely occurs in isolation and is often co-localized, especially in large urban areas.MethodsThe purpose of this study was to compare the effects of combined exposure to noise (N) or ozone (O3), compared to either exposure alone. Long-Evans dams were exposed to air or 0.4 ppm ozone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
5
9
0
Order By: Relevance
“…As in our previous reports [ 16 , 30 , 31 ], 0.8 ppm ozone inhalation for 4 h on the mornings of GDs 5 and 6 induced acute reductions in maternal food intake and body weight gain ( Table S2 ). However, peri-implantation ozone exposure had no effect on total gestational food intake, extrauterine body weight gain, or major litter characteristics such as the litter size and sex distribution ( Table S2 ).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…As in our previous reports [ 16 , 30 , 31 ], 0.8 ppm ozone inhalation for 4 h on the mornings of GDs 5 and 6 induced acute reductions in maternal food intake and body weight gain ( Table S2 ). However, peri-implantation ozone exposure had no effect on total gestational food intake, extrauterine body weight gain, or major litter characteristics such as the litter size and sex distribution ( Table S2 ).…”
Section: Resultssupporting
confidence: 80%
“…Prenatal exposure to air pollution is an emerging risk factor for the development of IUGR [ 4 ]. In our studies, we have consistently reported an enhanced male severity to growth restriction induced by peri-implantation inhalation to the gaseous air pollutant ozone [ 16 , 30 , 31 ]. Because of the exposure timing and chemistry of ozone, suppressed fetal growth is unlikely to be due to direct embryonic exposure to ozonation products (for example, lipid peroxides).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To investigate the impacts of ozone-induced FGR on the metabolic sensitivity in offspring, the 0.8 ppm concentration was selected for this study as lower concentrations (0.4 ppm) produce weight deficits only in male fetuses. 21,23 A reported four-to fivefold difference in heavy ( 18 O-labeled) reaction products in the lung exists between resting rats and intermittently exercising humans following ozone exposure. 35 Hence, the 0.8 ppm ozone concentration used herein corresponds to an approximated 0.16 ppm exposure in exercising humans, which is double the 2015 US EPA 0.07 ppm ozone standard.…”
Section: Maternal Ozone Exposurementioning
confidence: 99%